Analysis of Leadership Style, Workload, and Work Culture on Company Performance, With Work-Life Harmony as a Moderator. A Case Study of PT PLN UP3 Banyuwangi - Nur Rella Catur Trisno Wahyudi; Sri Gunani Partiwi (Eduvest - Journal of Universal Studies, 2026)
Organizations need to adapt proactively in the face of technological disruption and global uncertainty to sustain organizational performance. Human resource management has therefore become a key strategy, not only to achieve performance targets but also to maintain employee well-being and harmony between work and personal life. This study aims to examine the determinants of company performance by analyzing leadership style, workload, and work culture, with work-life harmony as a moderating variable, while also formulating evidence-based recommendations for human resource management policies. The study was conducted at PT PLN (Persero) UP3 Banyuwangi, which is characterized by a multigenerational workforce and high-performance targets. A quantitative approach was applied using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method through SmartPLS software. Data were collected from 84 employees using a digitally distributed Likert-scale questionnaire. The results indicate that leadership style, workload, and work culture do not have a significant direct effect on company performance. In contrast, work-life harmony has a positive and significant effect on performance (β = 0.825; p < 0.001). Furthermore, work-life harmony significantly moderates the relationship between leadership style and company performance (β = 0.233; p = 0.002), as well as the relationship between work culture and performance in a negative direction (β = −0.184; p = 0.021), while it does not significantly moderate the relationship between workload and performance.